2014
DOI: 10.1002/ana.24215
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association signal near NTN4 in Tourette syndrome

Abstract: Tourette Syndrome (TS) is a neurodevelopmental disorder with a complex genetic etiology. Through an international collaboration, we genotyped 42 single nucleotide polymorphisms (SNPs)(p<10−3) from the recent TS genome-wide association study (GWAS) in 609 independent cases and 610 ancestry-matched controls. Only rs2060546 on chromosome 12q22 (p=3.3×10−4) remained significant after Bonferroni correction. Meta-analysis with the original GWAS yielded the strongest association to date (p=5.8×10−7). Although its fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 21 publications
1
57
1
1
Order By: Relevance
“…No marker achieved genome-wide significance, though the strongest signal (p=1.85x10 -6 ) was located within an intron of COL27A1, the type XXVII collagen alpha chain gene 64 . A subsequent study of 42 of the top GWAS loci in 609 independent cases and 610 ancestry-matched controls revealed the most significant GTS association to date with a SNP lying closest to NTN4, an axon guidance molecule expressed in the developing striatum 65 .…”
Section: Hdcmentioning
confidence: 99%
See 1 more Smart Citation
“…No marker achieved genome-wide significance, though the strongest signal (p=1.85x10 -6 ) was located within an intron of COL27A1, the type XXVII collagen alpha chain gene 64 . A subsequent study of 42 of the top GWAS loci in 609 independent cases and 610 ancestry-matched controls revealed the most significant GTS association to date with a SNP lying closest to NTN4, an axon guidance molecule expressed in the developing striatum 65 .…”
Section: Hdcmentioning
confidence: 99%
“…As such, the success of GTS genetics will require continued expansion of international genetic collaborations and concerted efforts to identify innovative approaches to large-scale sample collection. On the collaborative front, US and European GTS genetics consortia have already harmonised phenotypic assessments and established pre-publication data sharing and joint meta-analyses 53,65 . For sample collection, multiple strategies are being pursued, including leveraging of data-rich electronic health records linked to biobanks 190 , identifying cases among population registry studies with available DNA 191 and development of validated, internet-based assessments combined with local biospecimen collection to bring sample collection to subjects, rather than focusing on collections limited to academic medical centres with GTS specialty clinics 192,193 .…”
Section: Thoughts For Dougmentioning
confidence: 99%
“…The one TS GWAS published to date (1496 cases and 5249 controls) has not pinpointed a statistically significant TS locus [83]. However, some sub-threshold GWAS peaks may still signal the involvement of variants fundamental to TS pathophysiology [84]. In the TS GWAS, Scharf et al found COL27A1 on chr 9q32 to have a strong association with TS ( p =1.85 × 10 −6 ) [83].…”
Section: Progression Of Genetic Studiesmentioning
confidence: 99%
“…Furthermore, Paschou et al . examined a top region from this GWAS in 609 cases and 610 controls and identified a single intergenic SNP (rs2060546) near the gene NTN4 that associated with TS; this finding remained statistically significant after Bonferroni correction [84]. NTN4 is believed to code for an axon guidance molecule in the developing striatum, an area implicated in TS; however, larger cohorts are required to confirm these findings [84].…”
Section: Progression Of Genetic Studiesmentioning
confidence: 99%
“…L-histamine decarboxylase, encoded by HDC gene, is the rate limiting enzyme in histamine synthesis. In addition, there may be some association of various single nucleotide polymorphisms (SNPs) noted by genome wide association studies (GWAS) involving proteins encoding axon guidance and outgrowth in the developing striatum [18]. …”
Section: Introductionmentioning
confidence: 99%